Synthesis, Antioxidant and Antibacterial Activities of Some Schiff Bases Containing Hydroxyl and Methoxy Groups - Al-Mamary, Mohammed; Ibrahim Abdelwahab, Siddig; Mohd Ali, Hapipah; Ismail, Salma; Ameen Abdulla, Mahmood; Darvish, Pouya (Asian Journal of Chemistry, 2012)
A series of Schiff bases were synthesized from different aromatic amines and aromatic aldehydes containing hydroxyl and methoxy groups. These compounds were characterized by IR and 1H NMR. All the compounds were screened for in vitro antioxidant activity using DPPH method and total reducing power activity based on the ability of compounds to reduce the Fe3+-TPTZ complex to the Fe2+/ferrous. Compounds substituted with hydroxyl and other electron donating groups, such as, methoxy groups showed low to high antioxidant activity. In addition, the compounds have been screened for their antibacterial activity against strains of Escherichia coli, Methycillin-resistant Staphylococcus aureus, Klebsiella pneumonia and Pseudomonas aeruginosa. The tested Schiff bases at 5 mg/disc showed different antibacterial activities depending on the type of the tested bacterial species. However, E. coli appeared to be sensitive to seven compounds (Ia, Ib, Ic, Id, If, IIb and IIe), while methicillin resistant Staphylococcus aureus (MRSA) was affected by Ic, Ie, IIc and IIe compound. On the other hand, the compounds Ia, Ic, Id, Ie and IIh revealed antibacterial activity against Klebsiella spp. The Pseudomonas aeruginosa was not sensitive to any of the tested Schiff bases.